An Exploration of the Pay Levels Needed to Attract Students with Mathematics, Science and Technology Skills to a Career in K-12 Teaching - Milanowski, Anthony (Education Policy Analysis Archives, 2003)
In an exploratory study (Note 1) of the role of salary level and other factors in motivating undergraduate math, science, and technology majors to consider a career as a K-12 teacher, the salary level students said would motivate them to consider a career in teaching was related to the salary expected in their chosen non-teaching occupation, but not to three of the Big 5 personality dimensions of extroversion, agreeableness, and openness, nor concern for others or career risk aversion. An annual starting salary 45% above the local average would attract 48% of the sophomore students and 37% of the juniors. Focus group results suggested that low pay was an important reason for not considering K-12 teaching, but that perceived job demands and abilities and interests were also important reasons for not being attracted to a teaching career.